2015
DOI: 10.7439/ijbar.v6i3.1833
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of blood donor deferral causes in a tertiary hospital, South India

Abstract: Aims: Transfusion of blood saves millions of life all over the world every year. Paucity of donors has always been a problem faced worldwide. Potential blood donors are deferred for several reasons. The rate and reasons of deferral differs from region to region and center to center. To ensure safe blood and blood products are provided by the blood bank, donors and recipients undergo stringent donor screening. All the donors are screened to ensure the blood drawn is safe for transfusion. Thus keeps the recipien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 10 publications
4
7
0
Order By: Relevance
“…Males (97.5%) and females (2.5%) constitutes total registered donor population, similar to other studies in literature. 6,7 The deferral rate among females was much higher when compared to males in current study similar to other studies in literarture. 8,9 Higher female deferral rate, low participation could be due to higher frequency of anemia, health problems, social taboos, cultural habits, lack of motivation, misbeliefs, reluctancy and fear to donate blood.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Males (97.5%) and females (2.5%) constitutes total registered donor population, similar to other studies in literature. 6,7 The deferral rate among females was much higher when compared to males in current study similar to other studies in literarture. 8,9 Higher female deferral rate, low participation could be due to higher frequency of anemia, health problems, social taboos, cultural habits, lack of motivation, misbeliefs, reluctancy and fear to donate blood.…”
Section: Discussionsupporting
confidence: 89%
“…The higher rate was due to inclusion of TTI seropositivity post donation similar to other studies in literature. 2,7,8,14 in contrast to lower rate reported by other studies. 11,13 Most common predonation cause of permanent deferral was hypertension 92 (76%) of donors.…”
Section: Discussionmentioning
confidence: 59%
“…Other causes include history of malaria, dengue or typhoid, dental procedures and vaccination. A study by John et al (2015) 24 26 reported their donor deferral rate to be 11.6%. This wavering seen in the donor deferral rates can be due to varying demographics of study population.…”
Section: Discussionmentioning
confidence: 99%
“…Safe and adequate supply of blood and blood products is a public health priority. According to national AIDS control organization's statistics, the annual rate of blood donation is about 7.4 million units against the requirement of 10 million units in India [1,2] Increasing awareness among people regarding blood transfusion has increased the number of voluntary donors over time. A voluntary donor is one who donates without any rewards or compulsion [3], whereas a replacement donor is one who donates blood upon request of specific patient or patient's family which intended to be used specifically for treatment of a patient [4].…”
Section: Introductionmentioning
confidence: 99%